PENGEMBANGAN MEDIA LEMBAR BALIK RUMAH BUDAYA INDONESIA UNTUK MENINGKATKAN PEMAHAMAN KEBERAGAMAN BUDAYA SISWA KELAS IV SDN BETET 1 - Revina Damayanti; Karimatus Saidah; Wahid Ibnu Zaman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the results of observations that have been conducted in grade IV SDN Betet 1 Kediri City, it is known that grade IV students have obstacles or difficulties in reading and memorizing various cultural diversities that exist in Indonesia. In addition, learning outcomes are also not optimal as indicated by the average value of students being less than the KKM value in the material of cultural diversity. This development research resulted in a learning media product, the Indonesian Cultural House Flip Sheet on the material of cultural diversity in grade IV SDN Betet 1. The research method used is the ADDIE development method. The results of the study show that this media has very good validity, with a value of 88% from media experts and 90% from material experts. The effectiveness of the media can be seen from the average student evaluation value which reached 86.6% in the limited test and 84.7% in the extensive trial, exceeding the minimum completeness criteria. Teacher and student responses also showed positive results, indicating this media is practical to use.